Respect Which Fonds? Personal Archives and Family Businesses in Nova Scotia - Barrett, Creighton (Archivaria, 2013)
Ongoing efforts to redefine and deconstruct the boundaries of archival theory are increasingly emphasizing personal archives, but a key issue has mostly been neglected: the natural presence of personal archives among the archives of corporate bodies. Even with a broadening conceptual framework of provenance, there is little theoretical or practical foundation from which to proceed with basic arrangement and description activities when personal archives and the archives of corporate bodies are intermingled. The archives of nineteenth- and twentieth-century family businesses in Nova Scotia are particularly good examples of aggregations of corporate records that include “hidden” personal archives. For many families that operated businesses, there was little or no distinction between personal recordkeeping and business or professional recordkeeping. Drawing on examples of personal archives found among family business records held at the Dalhousie University Archives in Halifax, this article demonstrates that materials of this nature challenge strict distinctions between personal archives and the archives of corporate bodies. It provides a discussion of provenance and the boundary of the fonds, and suggests that archivists may be working with hybrid aggregations of materials that can be attributed to individuals and corporate bodies. The article then introduces the concept of work identity, a work-centric identity formation that can be a useful perspective from which to consider how work influences the manner in which a person or family creates, accumulates, and uses records and information. RÉSUMÉ  Les efforts continus pour redéfinir et déconstruire les limites de la théorie archivistique accentuent davantage les archives personnelles, mais une question clé a été largement mise de côté : la présence naturelle des archives personnelles parmi les archives des entités corporatives. Même avec l’élargissement du cadre conceptuel par rapport à la provenance, les activités de classement et de description de base reposent sur des fondements peu solides lorsque les archives personnelles et les archives d’entités corporatives sont entremêlées. Les archives des entreprises familiales aux dix-neuvième et vingtième siècles en Nouvelle-Écosse sont de très bons exemples d’ensembles de documents corporatifs qui comprennent des archives personnelles « cachées ». Pour plusieurs familles qui dirigeaient des entreprises, il y avait peu ou pas de distinction entre la gestion de documents personnels et la gestion de documents d’affaires ou professionnels. En se servant d’exemples d’archives personnelles tirés des documents d’archives d’entreprises familiales conservées aux archives de l’Université Dalhousie à Halifax, cet article montre que ce genre de document conteste les distinctions claires et précises entre les archives personnelles et les archives d’entités corporatives. Il discute de la provenance et des limites du fonds d’archives et suggère que les archivistes peuvent travailler avec des collections de documents hybrides qui peuvent être attribués à la fois à des individus et à des entités corporatives. L’article introduit ensuite le concept d’identité du travail (« work identity »), la formation d’une identité centrée sur le travail, qui peut devenir une perspective utile à partir de laquelle on peut considérer comment le travail influence la façon dont une personne ou une famille crée, accumule et se sert des documents et de l’information.